Electro–ultrasonic coupled for enhanced removal efficiency of toxic fine particles from biomass combustion: Performance optimization and synergistic mechanisms - Hailin Gu; Zhengcheng Lou; Mingfeng Lu; Jiaqi Ran; Xu Wang; Chengxu Tu; Guangxue Zhang; Fubing Bao (Journal of Hazardous Materials, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

Multivariate data analysis of a severe air pollution event in Shihezi city, China - Feifan Chen; Qing He; Zhujun Zhao; Zhongqi Lu; Mingfeng Yang; Gang Ren; Jin Wang; Hongwei Zhang; Dongliang An; Chunxia Wu (Atmospheric Pollution Research, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Comparative study of failure mechanism of CFRP partially confined normal strength concrete (NSC) and UHPC cylinders under axial compression - Wanye Li; Yao Lu; Meizhong Wu; Peng Wang; Weiwen Li; Xingquan Wang; Mingfeng Kai; Jing Yu (Engineering Structures, 2025)

Effective reduction of hydrogen consumption in ultra-deep hydrodesulfurization of diesel: Deep insights into the effect of thermodynamic limitations during hydrotreating - Yubai Zhang; Feng Liu; Wenbin Chen; Wei Han; Weiming Zhai; Yutao Lu; Mingfeng Li (Fuel, 2024)

Numerical Simulation Study on Ship–Ship Interference in Formation Navigation in Full-Scale Brash Ice Channels - Chang Xie; Li Zhou; Mingfeng Lu; Shifeng Ding; Xu Zhou (Journal of Marine Science and Engineering, 2023)
Formation navigation in brash ice channels is increasingly utilized by merchant vessels in the Arctic and Baltic Sea, offering benefits such as improved efficiency and reduced carbon emissions. However, ship–ship interference poses a significant challenge to this method, impacting resistance performance. This paper presents full-scale simulations using the CFD–DEM coupling method in brash ice channels, which is validated by comparing simulation results with ice tank measurements. By varying the distance between two ships from 0.05 to 5 ship lengths, ship–ship interference in full-scale brash ice channels is analyzed using the CFD–DEM coupling strategy. The study examines hydrodynamic and ship–ice interactions, ice resistance effects, and simulation results. It is found that ship-to-ship distance significantly influences the velocity field, dynamic pressure distribution on the hull, and hydrodynamic interaction forces. Distances less than one ship length result in increased water resistance for the forward ship and decreased resistance for the rear ship. The forward ship demonstrates favorable interference with the ice accumulation of the rear ship. When distances are less than two ship lengths, the ice resistance of the forward ship remains mostly unaffected, while the ice resistance of the rear ship decreases as the distance decreases. These insights enhance our understanding of ship–ship interference in formation navigation, aiding in the optimization of brash ice channel navigation strategies.

Seasonal pollution and surface characteristics of microplastics in surface water in the Wanzhou section of the Three Gorges Reservoir, China - Ying He; Qian Huang; Qilong Wang; Mingfeng Tang; Xiaoyu Lu; Fei Cheng; Guosheng Xiao (Environmental Science and Pollution Research, 2023)
The pollution of freshwater environments with microplastics (MPs) has attracted increasing attention owing to their threats to aquatic ecosystems and human health. Here, we sampled and analyzed MPs from mainstream, tributary, and backwater areas in the Wanzhou section of the Three Gorges Reservoir (TGR) in impoundment and flood periods. Microplastic pollution was the most severe in the backwater areas. The average abundance of MPs reached the highest value in the flood period (5.27±3.47×10 7 items km −2 ), which was 3–5 times that in the impoundment period. In the 0.3–5 mm size class, the 1–5 mm fraction was the most abundant, accounting for more than 81% in the flood period and 68% of the total MP particle abundance in the impoundment period in the mainstream and backwater areas. However, 0.3–1 mm MPs contributed more than 50% in the tributaries during the impoundment period. Polystyrene, polypropylene, and polyethylene MPs were detected in foam, fragment, sheet, and line-shaped MP particles. White, opaque, foamed polystyrene MPs contributed 32–81% to total MP particle abundance in the watershed. Microplastic particle surfaces showed signs of damage and oxidation, and ten different elements were found. Oxygen was clustered on the surface of foam and fragment MPs. Microplastic pollution was severe in the Wanzhou watershed. Especially in the backwater areas, oxidized MPs of variable shapes derived mainly from surface runoff in the flood period and sewage discharge in the impoundment period were abundant. The results of this study contribute to understanding seasonal pollution patterns and surface characteristics of MPs in the TGR and similar watersheds.

Precursors and formation pathways of furfural in sugarcane juice during thermal treatment - Huimei Huang; Jiebo Chen; Mingfeng Zheng; Lulu Zhang; Hongfei Ji; Huajin Cao; Fengxia Dai; Lu Wang (Food Chemistry, 2023)

The genesis of the Ni–Cu sulfide mineralization of the carboniferous Haibaotan intrusion, Eastern Tianshan, Central Asian Orogenic Belt - Mingfeng Qiu; Yun Zhao; Chunji Xue; Jia Chen; Xiaoping Ma; Lu Wang; Liang Yu; Yanxiang You (International Journal of Earth Sciences, 2023)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Toward Improved Calibration of SWAT Using Season-Based Multi-Objective Optimization: a Case Study in the Jinjiang Basin in Southeastern China - Ying Chen; Xingwei Chen; Chong-Yu Xu; Mingfeng Zhang; Meibing Liu; Lu Gao (Water Resources Management, 2018)

Lipid desaturation in prokaryotic pathway abates the high-oleic phenotype of FAD2-silenced tobacco at lower temperature - Lulu Zhang; Heshu Lu; Chunmei Liu; Feiyan Xue; Jing Yang; Lanqing Ma; Mingfeng Yang (Journal of Plant Biochemistry and Biotechnology, 2016)